2007
DOI: 10.2139/ssrn.1862248
|View full text |Cite
|
Sign up to set email alerts
|

Human Capital and University-Industry Linkages’ Role in Fostering Firm Innovation: An Empirical Study of Chile and Colombia

Abstract: The Policy Research Working Paper Series disseminates the findings of work in progress to encourage the exchange of ideas about development issues. An objective of the series is to get the findings out quickly, even if the presentations are less than fully polished. The papers carry the names of the authors and should be cited accordingly. The findings, interpretations, and conclusions expressed in this paper are entirely those of the authors. They do not necessarily represent the views of the International Ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
22
0
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(25 citation statements)
references
References 6 publications
0
22
0
3
Order By: Relevance
“…The benefits of university-industry collaboration are also evident in developing countries. For example, a study in 2007 showed that collaboration with universities substantially increased the propensity of firms to introduce new products and to patent (Marotta, Mark, Blom, & Thorn, 2007).…”
Section: The Need For Curriculum Re-design In Universitiesmentioning
confidence: 99%
“…The benefits of university-industry collaboration are also evident in developing countries. For example, a study in 2007 showed that collaboration with universities substantially increased the propensity of firms to introduce new products and to patent (Marotta, Mark, Blom, & Thorn, 2007).…”
Section: The Need For Curriculum Re-design In Universitiesmentioning
confidence: 99%
“…Further, the role of knowledge in enterprise performance and countries' economic success has been addressed by researchers. The reason is that economic growth based on an increase in the number of resources is characterized by diminishing returns and is not sustainable (Marotta et al, 2007). This attracted attention to human capital and innovations as drivers of long-term economic growth.…”
Section: Introductionmentioning
confidence: 99%
“…Specifically, the idea behind endogenous growth models is that knowledge generates both the direct effects for a firm and spillovers from which the other firms in the economic benefit. Therefore aggregate production function demonstrates increasing returns to scale, making possible long-term economic growth (Marotta et al, 2007). We are interested in the quality of management, as it makes possible efficient use of the available technologies and can facilitate the creation of new knowledge.…”
Section: Introductionmentioning
confidence: 99%
“…In light of this information, resource dependency theory can explain the relationship between solidarity and innovation performance. In the related literature, small firms, which are weaker in terms of financial and human resources, appear to be more productive through university-industry solidarity (George, Zahra, & Wood, 2002;Hanel & St-Pierre, 2006;Marotta, Mark, Blom, & Thorn, 2007). It is emphasized that they can benefit from the creative and competent workforce who are not the actual employees at the current firms in order to create innovative products and services (Black & Lynch, 1996), and also stated that the firms that are in solidarity with the universities will be more effective in the innovation activities (Anatan, 2009).…”
Section: Introductionmentioning
confidence: 99%